Обман: повесть / Альберт Лиханов ; [художник Г. Новожилов] - Лиханов Альберт Анатольевич (Отрочество, 1981)
Экземпляры: ФО-7 (1982) / Инвентарный номер: 1901 / Авт.знак: Л 65 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6